Chitinase-like proteins promoting tumorigenesis through disruption of cell polarity via enlarged endosomal vesicles - Khalili, Dilan; Kunc, Martin; Herbrich, Sarah; Müller, Anna M.; Theopold, Ulrich (Frontiers in Oncology, 2023)
Introduction Chitinase-like proteins (CLPs) are associated with tissue-remodeling and inflammation but also with several disorders, including fibrosis, atherosclerosis, allergies, and cancer. However, CLP’s role in tumors is far from clear. Methods Here, we utilize Drosophila melanogaster and molecular genetics to investigate the function of CLPs (imaginal disc growth factors; Idgf’s) in RasV12 dysplastic salivary glands. Results and discussion We find one of the Idgf’s members, Idgf3, is transcriptionally induced in a JNK-dependent manner via a positive feedback loop mediated by reactive oxygen species (ROS). Moreover, Idgf3 accumulates in enlarged endosomal vesicles (EnVs) that promote tumor progression by disrupting cytoskeletal organization. The process is mediated via the downstream component, aSpectrin, which localizes to the EnVs. Our data provide new insight into CLP function in tumors and identifies specific targets for tumor control.